Proyecto De Vida Del Egresado Del Programa Licenciatura En Educación Física Y Deportes De La Universidad Del Quindío (2014)
This work as a research project of degree work is structured from the quantitative methodology of descriptive and transversal type, through a survey designed and approved by the academic vice-rector, with the objective of analyzing the impact of the life project of the A graduate of physical education and sports baccalaureate, was a process that was given through the application of a survey as a technique for gathering information, which was addressed to 103 graduates of the program Bachelor in Physical Education and Sports, their analysis was made to Through the statgraphic program, this research project was carried out in the first semester of 2014 and ended the second semester of 2014, this work is supported by different theories that allowed the orientation mainly for the analysis of its results where its main theories of the project of Life are supported from authors such as s Aez, E Fran and Gonzales D, and different divisions in the theoretical framework that are related to the theoretical references that the University of Quindío provides as well as the same degree program in physical education and sports, where one of the main conclusions of this project Was the work inside the program contributing to the project of life of the graduates because a 98.0% affirm that it was a successful process the step by the program of Degree in Physical Education and Sports to contribute to his project of life, Beforehand, Recommended to the University of Quindío, the Faculty of Education and the Degree Program in Physical Education and Sports, to promote more spaces where research by these processes of self-evaluation of the program, to continue supporting the interaction with graduates of Bachelor in Physical Education and Sports because of them depends the good results of the university to provide good profession To the work and social life and also to the committee of graduates, the construction of more activities for the graduates that motivate the participation of these in the program and do not leave aside the university, because of them also depends the success of the race Because you will know in advance the needs, shortcomings, skills of the program to continue working on optimizing this and be better every day.